EXPLORING CAREERS IN INFORMATION SECURITY. - Hartman, Shane (Career Planning & Adult Development Journal)
The article focuses on the career development in information security with the jobs available for data security and data protection. It mentions need to know how networking skills, understanding how routers and switches work and knowledge of Internet protocols like HTTP, and file transfer protocol (FTP). It also mentions need to learn operating system (OS) such as Windows and Ubuntu.